(untitled) (Filološke studije, 2019)
It is not that easy to write about the identity in the region such as Balkan. Many centuries of interference of cultures, traditions, languages, arrivals and departures of old civilizations are the cause of dispute, denial, changing and taking away someone’s identity. Artists and writers are just an example. Writing, primarily living in such environments, the writers have become a prey and therefore the victim of the political and national thoughts. Because of cultural interweaving, it is not hard to find in each one of them something "ours" and adopt it, but it is time to look at them in another way and to allow them to choose their own identities. The past is reminder of the millennial flows and connections between Serbian, Croatian, Bosnian and Yugoslavia culture. We should stop with taboos and stereotypes about where the writers belong to. We should understand and let their writings to speak about their identity. Besides being literary names, Ivo Andrić and Meša Selimović also are great creators who are surprising us with their inner strength and literary talent. Their greatness is one more reason why their names shouldn’t be used for political purposes. They wanted to belong ’there’ and ’here’. They should be the bridge that brings us together and not a bridge that separates us. We should let Andrić, Selimović and other writers to become the bridge that brings "our" coast, nation, culture, traditions and even the identities together.